2014
DOI: 10.1603/en13160
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Bt Rice Expressing Cry1C or Cry2A Protein on the Performance of Nontarget Leafhopper,Nephotettix cincticeps(Hemiptera: Cicadellidae), Under Laboratory and Field Conditions

Abstract: Transgenic rice expressing Bacillus thuringiensis Berliner (Bt) protein can effectively control target insects including stem borers and leaf folders. However, the potential effects of Bt rice on nontarget organisms including nontarget herbivores have not been fully evaluated. In the current study, ecological fitness parameters of the nontarget herbivore, Nephotettix cincticeps (Uhler) (Hemiptera: Cicadellidae), fed on T1C-19 (Cry1C) or T2A-1 (Cry2A) rice were compared with non-Bt rice (MH63) under laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…A series of investigations has been conducted to assess potential risks of transgenic Bt rice to non-target herbivores and their natural enemies, including parasitoids of pests in rice agroecosystems at population levels. For example, no adverse effects of Bt rice on fitness parameters (developmental duration, survival rate and fecundity) of non-target herbivorous insects, such as brown planthoppers (BPHs), leafhoppers, and soil collembolans, have been identified [9][10][11]. Similar results also were obtained in studies of fitness parameters of predatory Pardosa pseudoannulata, Ummeliata insecticeps, Cyrtorhinus lividipennis, Propylea japonoca and frogs [12][13][14][15][16].…”
Section: Introductionsupporting
confidence: 61%
“…A series of investigations has been conducted to assess potential risks of transgenic Bt rice to non-target herbivores and their natural enemies, including parasitoids of pests in rice agroecosystems at population levels. For example, no adverse effects of Bt rice on fitness parameters (developmental duration, survival rate and fecundity) of non-target herbivorous insects, such as brown planthoppers (BPHs), leafhoppers, and soil collembolans, have been identified [9][10][11]. Similar results also were obtained in studies of fitness parameters of predatory Pardosa pseudoannulata, Ummeliata insecticeps, Cyrtorhinus lividipennis, Propylea japonoca and frogs [12][13][14][15][16].…”
Section: Introductionsupporting
confidence: 61%
“…In laboratory assessments, several GRLH ecological fitness parameters, specifically nymphal duration, adult longevity, and fecundity were influenced by Bt rice, which varied according to the expressed insecticidal proteins, Cry1Ab [ 21 ], Cry2A or Cry1C [ 22 ]. Similarly, field investigations indicated that two types of Bt rice expressing a fused protein, Cry1Ab/Cy1Ac [ 23 , 24 ], or a single protein, Cry1Ab [ 21 ] resulted in a higher GRLH population density compared to the controls.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, field investigations indicated that two types of Bt rice expressing a fused protein, Cry1Ab/Cy1Ac [ 23 , 24 ], or a single protein, Cry1Ab [ 21 ] resulted in a higher GRLH population density compared to the controls. Other Bt rice lines expressing a fused Cry1Ab/Vip3H protein [ 25 ], or single Cry2A, or Cry1C proteins [ 22 ] showed no significant effects on population density.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pest natural enemies, other potential effects of Bt rice on nontarget herbivores also have been tested, focusing on planthoppers, leafhoppers and thrips. Laboratory studies showed that feeding on Bt rice producing Cry1Ac, Cry1Ab, Cry1C, Cry2A and vip3H proteins had no negative effect on survival and development of the planthoppers Nilaparvata lugens and Sogatella fucifera (Chen et al ., ; Fu et al ., ; Lu et al ., ,c, ; Mannakkara et al ., ; Zhang et al ., ). In accord with the results of laboratory studies, field trials did not find consistent differences in the population dynamics of planthoppers and thrips between Bt rice and nonrice fields (Akhtar et al ., ,b; Chen et al ., , ; Jiao et al ., ; Li et al ., ; Liu et al ., ,b; Romeis et al ., ;)…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 99%